PENENTUAN TEMPAT MENGINAP DENGAN MENGGUNAKAN FUZZY MULTIPLE ATTRIBUTE DECISION MAKING - Rima Aprilia; Triase Triase; Sriani Sriani (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2017)
AbstractThe problem of determining where to eat every seminar activities outside the city becomes a problem experienced by the participants of the seminar. In determining where to stay, decision support system using fuzzy multiple attribute is expected to provide the best solution in this case. The type of research is literature study by looking for reference theory relefan with cases or problems found. References that include general decision making, problem formulation, decision making of some fuzzy attributes, and generating a decision matrix that is expected to provide the best solution of the problem. These references can be searched from books, journals, research report articles, and websites on the internet. The output of this literature study collects reference that relefan with the formulation of the problem. The goal is to strengthen the process and also become the basis for designing decision support systemsKeywords: Dual Attribute Decision Making, TOPSIS, Weighted Product